A penetrating thoracoabdominal injury with arrow head: a case report - De, Suman; Dey, Rudra; Biswas, Siddhartha (International Surgery Journal, 2022)
Penetrating injuries to the chest present a frequent and challenging problem. The majority of these injuries can be managed non-operatively. The selection of patients for operation or observation can be made by clinical examination and appropriate investigations. A 17 years old male patient presented with an arrow inserted in his chest wall 5 cm. below right nipple. The patient was stable hemodynamically with no signs and symptoms of pneumothorax. Imaging of chest and abdomen, followed by laparotomy and removal of the arrow head from left lobe of liver performed.